How Important Is the New Goods Margin in International Trade? - Kehoe, Timothy J.; Ruhl, Kim J. (Journal of Political Economy, 2013)
We propose a methodology for studying changes in bilateral commodity trade due to goods not exported previously or exported only in small quantities. Using a panel of 1,900 country pairs, we find that increased trade of these “least-traded goods” is an important factor in trade growth. This extensive margin accounts for 10 percent of the growth in trade for NAFTA country pairs, for example, and 26 percent in trade between the United States and Chile, China, and Korea. Looking at country pairs with no major trade policy change or structural change, however, we find little change in the extensive margin.